Green oxidation of natural rubber latex using a sodium tungstate/formic acid/hydrogen peroxide catalytic system - Ninh, Tran Hai; Quyen, Le Thi; Giang, Le Duc; Hoan, Tran Nhu (Vietnam Journal of Chemistry, 2015)
The trialkylethylenic double bonds of natural rubber are well known to react very readily with peracids to yield epoxide groups. Hydrogen peroxide/formic acid system is one of effective stable catalysts with a broad scope for olefin epoxidations and alcohol oxidations because of its character of cheap, clean and give water as the sole byproducts. The tungsten complex serves as an excellent precatalyst, because it does not cause unproductive decomposition of H2O2. In this work, a catalytic system based on Na2WO4/HCOOH/H2O2 effectively oxidizes natural rubber (NR) in latex stage to prepare epoxidized natural rubber (ENR). The epoxidized polymers were characterized by DSC, FTIR, 1H-NMR and 13C-NMR analysis. The results showed that the Na2WO4/HCOOH/H2O2 catalytic system possesses much higher epoxidation efficiency than the traditional HCOOH/H2O2 system: the epoxidation degree (Xepoxy) of products increases from merely 9.6 % (HCOOH/H2O2) to values as high as 24.3 % (Na2WO4/HCOOH/H2O2) by reacting for 48 h at 25oC. The occurrence of secondary reactions to low extension could be detected by the presence of hydroxyl, carbonyl and alcohol signals in the spectra of epoxidized polymers. Keywords. Natural Rubber; Epoxidized Natural Rubber; Tungsten Complex Catalyst; FTIR; NMR.